Analysis of Risk Factors for Post-Hysterectomy Vaginal Vault Prolapse - Mahmut Kuntay kuntay Kokanali (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2015)
Purpose: To identify risk factors for vaginal vault prolapse after hysterectomy and also estimate incidence of post-hysterectomy vault prolapse. Material and Methods: This is a retrospective study of women who underwent hysterectomy for benign indications between January 2010 and December 2012. Medical records were reviewed from two groups of women. Case group was women who had undergone surgery for vault prolapse after hysterectomy; control group was women who were not identified with vault prolapse after hysterectomy by the time of the study. Multivariate regression model identified odds of post-hysterectomy vault prolapse. Results: Of 1758 hysterctomies, 56 (3.19%) were cases. Multivariate regression analysis demonstrated that age at hysterectomy and #8805;60 years, presence of asthma, previous pelvic organ prolapse surgery, vaginal route of hysterectomy, genital prolapse as indication of hysterectomy, body mass index and #8805;27 kg/m2 and number of vaginal delivery and #8805;2 are independent risk factors for development of post-hysterectomy vault prolapse. Conclusions: Vault prolapse after hysterectomy is a relatively rare complication. Elderly age, obesity, chronic obstructive lung diseases, prior genital prolapse sugery, vaginal hysterectomy, genital prolapse as indication of hysterectomy and the number of vaginal delivery and #8805;2 increase vault prolapse risk. Identification of these risk factors is important to prevent this complication. [Cukurova Med J 2015; 40(1.000): 63-71]